Making visible the dance: Strategies and tactics in teacher and student classroom interactions. Issue 3 (7th December 2015) - Rust, Julie
Abstract : Purpose: – This paper aims to delve deeply into the sometimes clashing interplays in English classrooms to explore the ways in which new media makes visible long-existing discourses and assumptions about the purpose of schools and the roles of teachers and students. Design/methodology/approach: – This piece draws upon discourse analysis and utilizes the frame of strategies versus tactics (de Certeau, 1984) to trace the complex classroom interplays between a high school English teacher, a partnering researcher and a high school junior during the process of a month-long digital photography project. Findings: – Data reveal that, at times, both teachers and students made moves to preserve the status quo of the school space (through strategies), and at other times, worked to reshape the space for more relevant purposes (through tactics.) Strategies that emerge from teacher moves include the formalization of requirements and the controlling of bodies; the student strategy described is the perpetuation of stereotypes. Teacher tactics reported include repositioning identities, reframing "the work" and opening up space for inquiry. Student tactics include resistance, shifting to the personal, subverting a given task and self-positioning. The author argues that generative potential exists at the intersection of teacher tactics and student tactics, and calls for furthering the co-construction of classroom spaces. Originality/value: – By zooming in on the process, rather than the product, that ensued as the focal student created and defended her photographs representing school as jail, this paper emphasizes the agency that both teachers and students can enact in sometimes limiting classroom spaces.